Associations between frontal lobe activity and depressive symptoms in patients with major depressive disorder receiving rTMS treatment: a near-infrared spectroscopy study - Chou, Po-Han; Liu, Wen-Chun; Wang, Shao-Cheng; Lin, Wei-Hao; Chung, Yi-Lun; Chang, Chun-Hung; Su, Kuan-Pin (Frontiers in Psychiatry, 2023)
The effects of repetitive transcranial magnetic stimulation (rTMS) on the left dorsolateral prefrontal cortex (DLPFC) in patients with major depressive disorder (MDD) have been proved to have antidepressant effects. However, the absence of biomarkers to assess treatment response remains a challenge. This research aims to explore the relationship between frontal lobe activity, measured using near infrared spectroscopy (NIRS), and changes in symptoms among MDD patients following rTMS treatment. A total of 26 MDD patients underwent 20 sessions of 10 Hz rTMS targeting the left DLPFC. NIRS was used to measure frontal lobe activity during a verbal fluency test at baseline, after 10 rTMS sessions, and after 20 rTMS sessions. Responders were defined as individuals with more than a 50% reduction in symptoms based on the 17-item Hamilton Depression Rating Scale after 20 rTMS sessions. Among the 14 responders, an increase in frontal lobe activity was significantly correlated with improvements in depressive symptoms following 10 (p = 0.0001) and 20 rTMS sessions (p = 0.007). Additionally, frontal lobe activity after 10 rTMS sessions was significantly associated with symptom improvement after 20 sessions (p = 0.001). These associations were not observed among non-responders. The findings from this study indicate distinct patterns of frontal lobe activity between responders and non-responders to rTMS treatment, suggesting that NIRS has the potential to serve as a biomarker for monitoring treatment response in MDD patients undergoing rTMS.